Life of the Navajo - Bishop, Amanda; Kalman, Bobbie (New York : Crabtree Pub. Co., 2004)
Describes the Navajo lifestyle, religion, and community as it existed when European explorers first arrived in the Southwest region of the United States. This work helps children learn about: the daily lives of Navajo men, women, and children; traditional beliefs, practices, and dwellings; the role of animals in the Navajo lifestyle; and more.
The Navajo people -- Harmony and respect -- Navajo communities -- Family life -- Marriage -- The lives of children -- At home in a hogan -- Food from the land -- The importance of animals -- Weaving -- Arts, crafts, and clothing -- Dangerous times -- Forced change -- The Navajo today.
Includes index
NC1010L
Keywords: Navajo Indians -- History; Navajo Indians -- Social life and customs; Indians of North America -- Southwest, New